Expectations, perceived purpose and preferences of Singaporeans in decision for medical informed consenting - Teo, Felicia Siok Ying (2017)
Importance Medical informed consent is a fundamental principle of healthcare which involves intercommunication between patient and doctor. Singapore is a multicultural society and therefore, the various socio demographic characteristics will affect the decisions made by Singaporeans towards healthcare. Despite Singapore’s world class healthcare system, there is still much effort needed to progress towards a patient-centric system. For better patient satisfaction in today’s competitive healthcare setting, there is a significant need to understand patients’ expectations, purpose and preferences towards medical informed consenting in healthcare. Objective Hence, this study aims to determine the expectations, perceived purpose and preferences of Singaporeans towards decision making and extent of information disclosure in healthcare, as well as identify social demographics with influential factors. Design, settings and participants An analysis was conducted on 451 respondents, aged 21 and above, over a 6-week period in a hospital environment. Results Most respondents preferred shared decision making, perceived consent forms for patient-centric purposes and expected doctors to reveal severe or death risks information. Socio demographic factors such as education, age, ethnicity and employment status were found to have an influence. Conclusion The findings would provide an insight for government agencies and health institutions to implement strategies for better patient satisfaction.